Kehidupan dan Pengaruh Simon Petrus dalam Teologi Kristen - Yakub Fransisko; Devi Lestary; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to examine the life and influence of Simon Petrus, one of the closest disciples of Jesus Christ, in the context of Christian theology. From an ordinary fisherman, Petrus underwent a significant transformation into an early Church leader, marked by the change of his name to